Techniques for Abdominal Wall Closure after Damage Control Laparotomy: From Temporary Abdominal Closure to Early/Delayed Fascial Closure—A Review - Qian Huang; Jieshou Li; Wan-yee Lau (Gastroenterology Research and Practice)
Open abdomen (OA) has been an effective treatment for abdominal catastrophes in traumatic and general surgery. However, management of patients with OA remains a formidable task for surgeons. The central goal of OA is closure of fascial defect as early as is clinically feasible without precipitating abdominal compartment syndrome. Historically, techniques such as packing, mesh, and vacuum-assisted closure have been developed to assist temporary abdominal closure, and techniques such as components separation, mesh-mediated traction, bridging fascial defect with permanent synthetic mesh, or biologic mesh have also been attempted to achieve early primary fascial closure, either alone or in combined use. The objective of this review is to present the challenges of these techniques for OA with a goal of early primary fascial closure, when the patient’s physiological condition allows.